First‐principles study, fabrication, and characterization of (Hf0.2Zr0.2Ta0.2Nb0.2Ti0.2)C high‐entropy ceramic - Ye, Beilin; Wen, Tongqi; Huang, Kehan; Wang, Cai‐Zhuang; Chu, Yanhui (Journal of the American Ceramic Society, 2019)
The formation possibility of (Hf0.2Zr0.2Ta0.2Nb0.2Ti0.2)C high‐entropy ceramic (HHC‐1) was first analyzed by the first‐principles calculations, and then, it was successfully fabricated by hot‐pressing sintering technique at 2073 K under a pressure of 30 MPa. The first‐principles calculation results showed that the mixing enthalpy and mixing entropy of HHC‐1 were −0.869 ± 0.290 kJ/mol and 0.805R, respectively. The experimental results showed that the as‐prepared HHC‐1 not only had an interesting single rock‐salt crystal structure of metal carbides but also possessed high compositional uniformity from nanoscale to microscale. By taking advantage of these unique features, it exhibited extremely high nanohardness of 40.6 ± 0.6 GPa and elastic modulus in the range from 514 ± 10 to 522 ± 10 GPa and relatively high electrical resistivity of 91 ± 1.3 μΩ·cm, which could be due to the presence of solid solution effects.